Partial dysfunction of Treg activation in sickle cell disease. Issue 3 (March 2014) - Vingert, Benoît; Tamagne, Marie; Desmarets, Maxime; Pakdaman, Sadaf; Elayeb, Rahma; Habibi, Anoosha; Bernaudin, Françoise; Galacteros, Frédéric; Bierling, Philippe; Noizat‐Pirenne, France; Cohen, José
<x xml:space="preserve">Abstract</x> Sickle cell disease (SCD) is a chronic inflammatory disease associated with multiple organ damage, chronic anemia, and infections. SCD patients have a high rate of alloimmunization against red blood cells (RBCs) following transfusion and may develop autoimmune diseases. Studies in mouse models have suggested that regulatory T cells (Treg) play a role in alloimmunization against RBC antigens. We characterized the phenotype and function of the Treg cell population in a homogeneous cohort of transfused SCD patients. We found that the distribution of Treg subpopulations differed significantly between SCD patients and healthy blood donors. SCD patients have a particular Treg phenotype, with strong CTLA‐4 and CD39 expression and weak HLA‐DR and CCR7 expression. Finally, we show that this particular phenotype is related to SCD rather than alloimmunization status. Indeed, we observed no difference in Treg phenotype or function in vitro using autologous feeder cells between strong and weak responders to alloimmunization. Am. J. Hematol. 89:261–266, 2014. © 2013 Wiley Periodicals, Inc.